Pengembangan Bahan Ajar Menulis Ilmiah Berbasis Teks Melalui ADDIE Model pada Mahasiswa Prodi Pendidikan Bahasa dan Sastra Indonesia FKIP Universitas Jambi 2017/2018 - Andiopenta Purba (Jurnal Ilmiah Dikdaya, 2021)
The purpose of this research is to describe; (1) Text-based Scientific Writing syllabus model, and (2) Text-based Scientific Writing teaching materials model. The research method used is the EDDIE model development research method. Data were collected using a questionnaire technique, for the students of the Indonesian Language and Literature Education Study Program, Jambi University, class of 2017/2018 as many as 40 respondents for the experimental class and 40 for the control class. The results of the study consisted of the syllabus and material. After being tested, it turned out that the teaching materials produced were suitable for use. Research conclusions; (1) The contents of the course syllabus for Writing Scientific Reports that are produced are in accordance with the needs of students. (2) The contents of the scientific report writing teaching materials produced from this study are very suitable to the needs of students. And (3) The syllabus and teaching materials for writing scientific reports produced in this study are feasible and effective in learning Scientific Report Writing at the Indonesian Language and Literature Education Study Program, FKIP, Jambi University.